The role of serine metabolism in lung cancer: From oncogenesis to tumor treatment - Zhou, Xijia; Tian, Chang; Cao, Yingshu; Zhao, Min; Wang, Ke (Frontiers in Genetics, 2023)
Metabolic reprogramming is one of the important hallmarks of malignant tumors. Serine is a non-essential amino acid involved in cell proliferation. Serine metabolism, especially the de novo serine synthesis pathway, forms a metabolic network with glycolysis, folic acid cycle, and one-carbon metabolism, which is essential to rapidly proliferating cells. Due to the rapid development of metabolomics, abnormal serine metabolism may serve as biomarkers for early diagnosis and pathological typing of tumors. And targeting serine metabolism also plays an essential role in precision and personalized therapy for cancers. This article is a systematic review of serine metabolism in tumorigenesis, especially in lung cancer. In addition, we also discuss the potential to exploit serine metabolism to improve tumor treatment.